The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fpls.2015.01119
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA390-Directed TAS3 Cleavage Leads to the Production of tasiRNA-ARF3/4 During Somatic Embryogenesis in Dimocarpus longan Lour

Abstract: Trans-acting short-interfering RNAs (tasiRNAs) originate from TAS3 families through microRNA (miRNA) 390-guided cleavage of primary transcripts and target auxin response factors (ARF3/-4), which are involved in the normal development of lateral roots and flowers in plants. However, their roles in embryo development are still unclear. Here, the pathway miR390-TAS3-ARF3/-4 was identified systematically for the first time during somatic embryo development in Dimocarpus longan. We identified the miR390 primary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…The auxin-related miRNAs frequently target the fundamental components of the auxin signaling pathway, including the ARFs, which are involved in SE induction [27,93]. Accordingly, insights into embryogenic cultures of Arabidopsis and other plants indicated that miR160 could directly regulate the expression of ARF10, ARF16, and ARF17; miR167 seems to the control expression of ARF6 and ARF8, while miR390 possibly downregulates the ARF2, ARF3, ARF4 transcripts [55,63,64,68,81,85,86].…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…The auxin-related miRNAs frequently target the fundamental components of the auxin signaling pathway, including the ARFs, which are involved in SE induction [27,93]. Accordingly, insights into embryogenic cultures of Arabidopsis and other plants indicated that miR160 could directly regulate the expression of ARF10, ARF16, and ARF17; miR167 seems to the control expression of ARF6 and ARF8, while miR390 possibly downregulates the ARF2, ARF3, ARF4 transcripts [55,63,64,68,81,85,86].…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…Similar to the widely documented involvement of miRNA molecules in plant development in vivo (Jin et al, 2013), the expression of miRNAs was reported during in vitro induced SE in several plant species including Citrus sinensis, Dimocarpus longan, Gossypium hirsutum, Larix kaempferi, Larix leptolepis, Liriodendron tulipifera × L. chinense, Manihot esculenta , and Zea mays (Zhang et al, 2012, 2014; Li et al, 2013; Lin and Lai, 2013; Yang et al, 2013; Chávez-Hernández et al, 2015; Wu et al, 2015; Lin et al, 2015a,b; Khatabi et al, 2016). Thus, the engagement of miRNAs in the embryogenic transition that is induced in vitro is assumed, although knowledge about the function of the specific miRNA in SE induction is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Many other genes were found associated with heat stress such as gibberellin 2-oxidase 8 which regulates plant growth (Lo et al, 2008), ethylene-regulated nuclear protein (ERT2), which regulates plant growth and development through cell elongation and cell division (Sakai et al, 1998), ABC-2 type transporter family protein is involved in plant growth, development and response to abiotic stresses (Kang et al, 2011). Other genes associated with plant growth and development such as C2H2-like zinc finger protein (Chrispeels et al, 2000), iron regulated 2 , and core-2/I-branching beta-1,6-Nacetylglucosaminyltransferase family protein (Lin et al, 2015) were also identified.…”
Section: Discussionmentioning
confidence: 99%
“…Many candidate genes were identified that are associated with raceme height and are involved in different physiological process. Of these candidate genes, Core-2/Ibranching beta-1,6-N-acetylglucosaminyltransferase family proteins involved in plant development (Lin et al, 2015), plant calmodulin-binding protein is associated with Ca2+ binding and plant growth (Ranty et al, 2006), indoleacetic acid-induced protein 10 which enhances plant growth under drought stress condition (Yasin et al, 2006), protein kinase family protein involved in stem elongation and vascular development (Matschi et al, 2013), auxin response factor 1 regulates plant growth and development (Li et al, 2016), mitogen-activated protein kinase acts as signal transporter for cell division and plant growth (Sinha et al, 2011), AP2/B3-like transcriptional factor family protein is involved in plant growth , ACC oxidase 1 is involved in plant growth and lowering stress susceptibility ( Van de Poel and Van Der Straeten, 2014).…”
Section: Discussionmentioning
confidence: 99%